Seminar Parenting Penanaman Karakter Disiplin melalui Keteladanan pada Anak - Dian Rustyawati; Sholikah, Sholikah; Maula, I’nayatul; Suhanto, Ahmad; Fatimah, Fitri (INCOME: Indonesian Journal of Community Service and Engagement, 2024)
The development of the times and the rapid flow of globalization and the development of information technology are challenges in children's education and parenting. One of the things that needs to be taught to children is discipline. Disciplinary character needs to be cultivated because it affects attitudes, morals, respect for time, and other people. The role of parents is needed in fostering children's disciplinary character, such as in providing examples and implementing disciplinary rules. The purpose of this community service activity is to increase parents' understanding of the importance of implementing parenting patterns that teach discipline to children. The method of implementing this community service activity is carried out by presenting material to parents of grade 5 & 6 students of Yayasan Al-Azhar Sendanghaji Kec. Merakurak Tuban. The result of the community service activity is that student guardians better understand the importance of implementing parenting that teaches discipline through exemplary behavior from parents to children.